2000
DOI: 10.1002/1097-0045(20000901)44:4<275::aid-pros3>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of androgen-independent prostate cancer using antimicrotubule agents docetaxel and estramustine in combination: an experimental study

Abstract: BACKGROUND.Estramustine in combination with other chemotherapeutic agents has demonstrated synergy in hormone-refractory prostate cancer. Docetaxel has demonstrated antineoplastic activity in a variety of chemotherapeutic-unresponsive tumors. We evaluated the effects of estramustine and docetaxel in preclinical models of prostate cancer. METHODS. Cell viability of PC-3 and MAT-LyLu (MLL) cells were assessed 48 hr after drug treatment. For in vivo studies, each flank of five animals in six groups was injected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 11 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…Docetaxel inhibits tumor growth by the induction of microtubule stabilization and the promotion of bcl-2 inactivation, which effects induce apoptosis. 9,10 Docetaxel has an obvious anti-tumor effect on prostate cancer cells, 11,12 and it has been used clinically in HRPC patients. In 1999, Picus and Schultz 13 demonstrated that 75 mg/m 2 docetaxel treatment every 3 weeks had a significant effect in HRPC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Docetaxel inhibits tumor growth by the induction of microtubule stabilization and the promotion of bcl-2 inactivation, which effects induce apoptosis. 9,10 Docetaxel has an obvious anti-tumor effect on prostate cancer cells, 11,12 and it has been used clinically in HRPC patients. In 1999, Picus and Schultz 13 demonstrated that 75 mg/m 2 docetaxel treatment every 3 weeks had a significant effect in HRPC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The most active agent preclinically and clinically was docetaxel, either alone or in combination with estramustine. [28][29][30] Docetaxel, a semisynthetic taxane, likely has multiple mechanisms of antineoplastic activity. Microtubule stabilization, the most widely accepted mechanism of action, involves binding of docetaxel to ␤-tubulin, thus promoting polymerization (Figure 3).…”
Section: Chemotherapy For Hormone Refractory Prostate Cancer: the Taxmentioning
confidence: 89%
“…32,33 DCT concentration (1-100 nM) in this study was set up considering its reported IC 50 values in PC-3 cells. [34][35][36] Cell viability was measured using an MTS-based assay after 48 and 72 hours of incubation of Taxotere and PS-PDLLA/ DCT NPs. At all DCT concentration (1, 10 and 100 nM) and incubation time (48 and 72 hours) groups, the cell viability (%) of the PS-PDLLA/DCT NP-treated group was lower than that of the Taxotere group (P0.05).…”
Section: In Vitro Anti-tumor Efficacymentioning
confidence: 99%